2023
DOI: 10.3390/e25020338
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Tourist Arrivals for Hainan Island in China with Decomposed Broad Learning before the COVID-19 Pandemic

Abstract: This study proposes a decomposed broad learning model to improve the forecasting accuracy for tourism arrivals on Hainan Island in China. With decomposed broad learning, we predicted monthly tourist arrivals from 12 countries to Hainan Island. We compared the actual tourist arrivals to Hainan from the US with the predicted tourist arrivals using three models (FEWT-BL: fuzzy entropy empirical wavelet transform-based broad learning; BL: broad Learning; BPNN: back propagation neural network). The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is important to investigate the use of other types of models to forecast the BWTSD and compare their performance. Recent studies have shown that hybrid models combining ARIMA with artificial intelligence (AI) algorithms have produced superior results in predicting insect populations (Chen et al, 2023;Zhao et al, 2023). In addition, it would be worthwhile to compare the performance of ARIMA models with other time series forecasting techniques such as exponential smoothing or seasonal decomposition (Svetunkov et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to investigate the use of other types of models to forecast the BWTSD and compare their performance. Recent studies have shown that hybrid models combining ARIMA with artificial intelligence (AI) algorithms have produced superior results in predicting insect populations (Chen et al, 2023;Zhao et al, 2023). In addition, it would be worthwhile to compare the performance of ARIMA models with other time series forecasting techniques such as exponential smoothing or seasonal decomposition (Svetunkov et al, 2023).…”
Section: Resultsmentioning
confidence: 99%